2015
DOI: 10.1038/cddis.2015.262
|View full text |Cite
|
Sign up to set email alerts
|

EphB3 receptors function as dependence receptors to mediate oligodendrocyte cell death following contusive spinal cord injury

Abstract: We demonstrate that EphB3 receptors mediate oligodendrocyte (OL) cell death in the injured spinal cord through dependence receptor mechanism. OLs in the adult spinal cord express EphB3 as well as other members of the Eph receptor family. Spinal cord injury (SCI) is associated with tissue damage, cellular loss and disturbances in EphB3-ephrinB3 protein balance acutely (days) after the initial impact creating an environment for a dependence receptor-mediated cell death to occur. Genetic ablation of EphB3 promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…The Eph-family consists of 14 receptors, divided into two subclasses, EphA and EphB, based on their preference for ligand binding. Ephs and ephrins of both subclasses are expressed on oligodendrocytes (Linneberg, Harboe, & Laursen, 2015;Prestoz et al, 2004;Tsenkina et al, 2015), and in vitro data indicate that signaling through EphA or EphB in the oligodendrocyte prevents process extension, whereas signaling though ephrin-B enhances myelin sheet formation (Linneberg et al, 2015). However, there are exceptions to this, as EphA4 has also been reported to interact with ephrin-B (Kullander & Klein, 2002), albeit with a 10-fold lower affinity (Qin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eph-family consists of 14 receptors, divided into two subclasses, EphA and EphB, based on their preference for ligand binding. Ephs and ephrins of both subclasses are expressed on oligodendrocytes (Linneberg, Harboe, & Laursen, 2015;Prestoz et al, 2004;Tsenkina et al, 2015), and in vitro data indicate that signaling through EphA or EphB in the oligodendrocyte prevents process extension, whereas signaling though ephrin-B enhances myelin sheet formation (Linneberg et al, 2015). However, there are exceptions to this, as EphA4 has also been reported to interact with ephrin-B (Kullander & Klein, 2002), albeit with a 10-fold lower affinity (Qin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are exceptions to this, as EphA4 has also been reported to interact with ephrin-B (Kullander & Klein, 2002), albeit with a 10-fold lower affinity (Qin et al, 2010). Ephs and ephrins of both subclasses are expressed on oligodendrocytes (Linneberg, Harboe, & Laursen, 2015;Prestoz et al, 2004;Tsenkina et al, 2015), and in vitro data indicate that signaling through EphA or EphB in the oligodendrocyte prevents process extension, whereas signaling though ephrin-B enhances myelin sheet formation (Linneberg et al, 2015). How the individual members of the Eph-ephrin families might be involved in the myelination process is, however, unknown.…”
mentioning
confidence: 99%
“…It was revealed that ephrin-B3 is expressed in postnatal myelinating oligodendrocytes and acts as myelin-based inhibitor through a combined p75 neurotrophin receptor ( 136 ). A previous study demonstrated that EphB3 functions as a dependence receptor that mediates oligodendrocyte cell death following SCI, which further supports the development of ephrin-B3 based therapies to promote recovery ( 137 ).…”
Section: Expression and Regulation Of Eph Receptors And Ephrins In Thmentioning
confidence: 57%
“…In recent years, Eph receptors have been found to have pro-apoptotic responses following traumatic central nervous system (CNS) injury 19 21 , and are now classified as new members of a larger “dependence receptor” family 22 . Dependence receptors are transmembrane proteins that have dual opposing roles depending on the availability of their corresponding ligand.…”
Section: Introductionmentioning
confidence: 99%
“…When the ligand is present, these receptors can promote normal development and tissue homeostasis by inducing ligand-mediated positive signals 24 , 25 . Currently, two Eph receptors, EphA4 and EphB3, have been found to have dependence receptor functions in the naive and injured adult CNS 20 , 21 , 23 , 26 . Here, we describe a new dependence receptor role for EphB3 in regulating cerebral vascular EC survival after TBI.…”
Section: Introductionmentioning
confidence: 99%